Extended Darboux frame curvatures of Frenet curves lying on parametric 3-surfaces - Uyar Düldül, Bahar; Düldül, Mustafa (Kuwait Journal of Science, 2019)
In this paper, we consider a Frenet curve lying on a parametric hypersurface in 4-dimensional Euclidean space and obtain the expressions of its curvatures with respect to the hypersurface